Spherical graphite-silicon-carbon composite material and preparation method and application thereof

Through electrostatic adsorption and asphalt-based carbon coating, the dispersion and volume expansion problems of nanosilicon and microspherical graphite are solved, and a high-performance spherical graphite @silicon @carbon composite material is prepared, which improves the cycle stability and lithium storage specific capacity of lithium-ion batteries.

CN120440899AInactive Publication Date: 2025-08-08SHAANXI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510613126.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-08-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among the existing lithium-ion battery negative electrode materials, nano-silicon and microspherical graphite have poor dispersion, and the volume expansion problem of silicon has not been effectively solved, resulting in attenuation of cyclic performance, and high toxicity of organic monomers and high operation difficulty.

Method used

Nanosilicon is used as the basic structural unit, and the surface modification is positively charged, combined with the negatively charged electrostatic adsorption of the microspherical graphite surface, and a sandwich structure is formed by asphalt-based carbon coating to ensure the dispersion and stability of nanosilicon on the spherical graphite surface.

Benefits of technology

The uniform dispersion of nano-silicon on the microspherical graphite surface is achieved, which alleviates the problem of volume expansion and improves the circulation stability and lithium storage specific capacity of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120440899A_ABST
    Figure CN120440899A_ABST
Patent Text Reader

Abstract

The invention discloses a spherical graphite-silicon-carbon composite material as well as a preparation method and application thereof, and belongs to the technical field of lithium ion battery materials. The method comprises the following steps: preparing a micron spherical graphite modified product A with negative charges; preparing a nanometer silicon modified product B with positive charges; mixing the micron spherical graphite modified product A with negative charges and the nano silicon modified product B with positive charges, filtering, and drying to obtain a spherical graphite and silicon composite material; immersing the spherical graphite and silicon composite material into an asphalt solution, heating to a set temperature, and evaporating while stirring until the solvent is completely evaporated to obtain an intermediate product; and carrying out high-temperature calcination on the intermediate product to obtain the spherical graphite-silicon-carbon composite material. According to the preparation method, nano silicon is directly used as a basic structure unit, so that the problems of high toxicity of organic monomers, difficulty in operation and the like in the prior art are solved, meanwhile, a spherical graphite-silicon-carbon preparation process is designed aiming at the problems of dispersion of nano silicon and micron spherical graphite and silicon volume expansion, effective dispersion of silicon is ensured, and the volume expansion of silicon is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion battery materials, and specifically relates to a spherical graphite@silicon@carbon composite material and a preparation method and application thereof. Background Art

[0002] The anode is a crucial component of lithium-ion batteries, and the vast majority of these batteries utilize graphite. Currently, commercially available graphite for lithium-ion batteries is primarily spherical graphite, and while its preparation technology is relatively mature, its theoretical specific capacity is only 372 mAh / g, making it difficult to meet the high-energy-density demands of the power battery market. Among current anode material systems, silicon, with its alloy lithium storage mechanism, is widely favored, boasting a theoretical specific capacity of up to 4200 mAh / g, over ten times higher than that of graphite anodes. However, silicon's low conductivity necessitates its use in nanoparticle form, while commercially available spherical graphite is typically around 15 μm in diameter. This poses a significant challenge in the development of high-performance silicon-carbon composites. Furthermore, silicon's high theoretical specific capacity comes at the expense of a significant volume expansion of up to 300%. This makes it susceptible to volume expansion and fragmentation during charge and discharge, leading to cycling performance degradation. Therefore, ensuring close contact between the silicon and spherical graphite while ensuring the dispersion of the silicon particles is a second challenge in developing high-performance silicon-carbon composites.

[0003] For example, the Chinese invention patent with the existing publication number CN110931744A provides a silicon-carbon negative electrode material and its preparation method, which uses organic monomers as silicon sources to prepare silicon-carbon composite materials. Small molecular monomers such as formaldehyde and acetaldehyde are used in the preparation process to form a silicon-carbon negative electrode material with a high-porosity network-like coating structure after carbonization. Although the porous structure can effectively buffer the volume expansion of silicon during the lithium insertion and extraction process, organic substances such as silicone and formaldehyde are highly toxic and carcinogenic during use, and their practical application needs to be further optimized. Summary of the Invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a spherical graphite@silicon@carbon composite material and its preparation method and application. The preparation method directly uses nanosilicon as the basic structural unit to solve the problems of high toxicity and difficult operation of organic monomers in the prior art. At the same time, in order to solve the dispersion problems of nanosilicon and micron spherical graphite and the volume expansion of silicon, a preparation process of spherical graphite@silicon@carbon is designed to ensure the effective dispersion of silicon and alleviate its volume expansion.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a spherical graphite@silicon@carbon composite material, comprising the following steps: The micron spherical graphite and the acid solution are mixed and stirred to perform surface functional modification on the micron spherical graphite to obtain a negatively charged micron spherical graphite modified product A; The nano-silicon particles and the cationic surfactant solution are mixed and stirred to perform surface functional modification on the nano-silicon particles to obtain a nano-silicon modified product B with a positive charge; A negatively charged micron spherical graphite modified product A and a positively charged nano-silicon modified product B are mixed, the positively charged nano-silicon modified product B is dispersed and attached on the surface of the negatively charged micron spherical graphite modified product A, and a spherical graphite@silicon composite material is obtained after filtering and drying; The spherical graphite@silicon composite material is immersed in an asphalt solution, and then the solution is heated to a set temperature while being stirred and evaporated until the solvent is completely evaporated to obtain an intermediate product; The intermediate product is calcined at high temperature to obtain a spherical graphite@silicon@carbon composite material.

[0006] In one embodiment, the acid solution is one or more of a sulfuric acid solution, a hydrochloric acid solution, and a nitric acid solution, and the mass fraction of the acid solution is 5-20 wt%.

[0007] In one embodiment, the ratio of the micron spherical graphite to the acid solution is 1 g: (2-10) mL.

[0008] In one embodiment, the cationic surfactant in the cationic surfactant solution is one of octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, phenoxyethanol quaternary ammonium salt, succinic acid monoester quaternary ammonium salt, and 3-aminopropyltriethoxysilane; the solvent in the cationic surfactant solution is water; and the mass fraction of the cationic surfactant solution is 5 to 20 wt%.

[0009] In one embodiment, the ratio of the nano-silicon particles to the cationic surfactant solution is 1 g: (2-10) mL.

[0010] In one embodiment, the mass ratio of the micron spherical graphite to the nano-silicon particles is 100:(5-15).

[0011] In one embodiment, the asphalt solution is prepared by compounding asphalt and tetrahydrofuran solution, and the mass fraction of asphalt is 5-15wt%; the usage ratio of spherical graphite@silicon composite material to asphalt solution is 1g: (0.5-5)mL.

[0012] In one embodiment, when the spherical graphite@silicon composite material is immersed in the asphalt solution, the temperature of the asphalt solution is 50-80°C; the set temperature is 50-80°C; The atmosphere for high-temperature calcination is nitrogen, argon or argon-hydrogen mixed gas, the temperature for high-temperature calcination is 550~800℃, and the time for high-temperature calcination is 30min~2h.

[0013] The present invention also provides a spherical graphite@silicon@carbon composite material prepared by the above-mentioned preparation method of the spherical graphite@silicon@carbon composite material. The structure of the spherical graphite@silicon@carbon composite material is a sandwich structure with spherical graphite as the core, silicon attached to the surface of the spherical graphite, and further coated with asphalt-based carbon.

[0014] The present invention also provides a use of a spherical graphite@silicon@carbon composite material prepared by the above-mentioned preparation method of the spherical graphite@silicon@carbon composite material as a negative electrode material in a lithium ion battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for preparing a spherical graphite, silicon, and carbon composite material. This method directly utilizes nanosilicon as a structural unit, eliminating the additional steps required to prepare nanosilicon from an organosilicon precursor and simplifying the process. To ensure uniform dispersion of the nanosilicon and micron-sized spherical graphite, the nanosilicon particles and spherical graphite are pre-treated to impart opposite charges to their surfaces. Electrostatic attraction allows the nanosilicon to be adsorbed onto the surface of the micron-sized spherical graphite. The uniform dispersion of the nanosilicon is ensured by adjusting the ratio of the two and the reaction conditions. Furthermore, given that electrostatic adsorption is difficult to effectively alleviate the volume expansion problem of nano-silicon negative electrode during the cycle, the present invention further immerses the obtained spherical graphite@silicon composite material in an asphalt solution, and uses the carbonization process to wrap a layer of carbon shell on the surface of the spherical graphite@silicon composite material, thereby forming a multi-layer composite structure of spherical graphite@silicon@carbon, forming a sandwich structure with a spherical graphite core, silicon attached to the surface, and further coated with asphalt-based carbon. With the help of this structure, nano-silicon is anchored and its volume expansion during lithium intercalation and deintercalation is alleviated. This method not only realizes the dispersion of nano-silicon on the surface of spherical graphite, but also ensures the structural stability of nano-silicon during lithium intercalation and deintercalation, and ultimately improves the cycle stability of the composite material during lithium storage.

[0016] The present invention also provides a spherical graphite@silicon@carbon composite material prepared by the preparation method of the above-mentioned spherical graphite@silicon@carbon composite material. The problem of nano-scale silicon being difficult to effectively disperse in micron-scale spherical graphite is avoided through electrostatic action. At the same time, the spherical graphite@silicon composite material is secondary coated with the effect of asphalt-based carbon to improve the overall structural stability of the composite material, so as to ensure the cycle stability of the battery when it is finally used in lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1This is a comparison chart of the cycling performance of the spherical graphite@silicon@carbon composite material prepared in Example 1 of the present invention and the spherical graphite@silicon composite material prepared in Comparative Example 1; Figure 2 This is a comparison chart of the cycling performance of the spherical graphite@silicon@carbon composite material prepared in Example 2 of the present invention and the spherical graphite@silicon composite material prepared in Comparative Example 2; Figure 3 This is a comparison chart of the cycling performance of the spherical graphite@silicon@carbon composite material prepared in Example 3 of the present invention and the spherical graphite@silicon@carbon composite material prepared in Comparative Example 3; Figure 4 This is an SEM image of the spherical graphite@silicon@carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] To facilitate understanding of the features and effects of the present invention by those skilled in the art, the following provides a general description and definition of the terms and expressions used in the specification and claims. Unless otherwise indicated, all technical and scientific terms used herein have the ordinary meanings as understood by those skilled in the art regarding the present invention. In the event of conflict, the definitions in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] All features, such as values, amounts, contents, and concentrations, described herein as numerical ranges or percentage ranges are provided for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to include and specifically disclose all possible subranges and individual values within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “include,” “including,” “contains,” “has” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, for the sake of brevity, not all possible combinations of the various technical features in each embodiment or example are described. Therefore, as long as there are no contradictions in the combination of these technical features, the various technical features in each embodiment or example can be combined in any way, and all possible combinations should be considered to be within the scope of this specification.

[0023] In one aspect, the present invention provides a method for preparing a spherical graphite@silicon@carbon composite material, comprising the following steps: S1: mixing and stirring micron-sized spherical graphite and an acid solution to functionalize the surface of the micron-sized spherical graphite to obtain a negatively charged micron-sized spherical graphite modified product A; S2: mixing and stirring the nano-silicon particles and the cationic surfactant solution to functionalize the surface of the nano-silicon particles to obtain a positively charged nano-silicon modified product B; S3: Mixing the negatively charged micron-sized spherical graphite modified product A and the positively charged nano-silicon modified product B, and using the electrostatic force between the positive and negative charges to ensure the dispersion and attachment of nano-sized silicon particles on the surface of the micron-sized spherical graphite, and filtering and drying to obtain a spherical graphite@silicon composite material; S4: dispersing the spherical graphite@silicon composite material into the asphalt solution, raising the temperature to a set temperature while stirring and evaporating until the solvent is completely evaporated to obtain an intermediate product; S5: calcining the intermediate product at a high temperature under an inert atmosphere to obtain a spherical graphite@silicon@carbon composite material.

[0024] In a specific implementation process, in S1, the acid solution is one or more of sulfuric acid solution, hydrochloric acid solution, and nitric acid solution, and the mass fraction of the acid solution is 5-20wt%.

[0025] In a specific implementation process, in S1, the ratio of the micron spherical graphite to the acid solution is 1 g: (2-10) mL, the stirring speed is 100-300 rpm, and the stirring time is 20-200 min.

[0026] In the specific implementation process, in S2, the cationic surfactant in the cationic surfactant solution is one of octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, phenoxyethanol quaternary ammonium salt, succinic acid monoester quaternary ammonium salt, and 3-aminopropyltriethoxysilane, and the solvent in the cationic surfactant solution is water; the mass fraction of the cationic surfactant solution is 5~20wt%.

[0027] In a specific implementation process, in S2, the dosage ratio of the nano-silicon particles to the cationic surfactant solution is 1 g: (2-10) mL, the stirring speed is 100-300 rpm, and the stirring time is 20-200 min.

[0028] In a specific implementation process, in S3, the mass ratio of micron spherical graphite to nano silicon particles is 100:(5~15).

[0029] In the specific implementation process, in S3, the negatively charged micron spherical graphite modified product A and the positively charged nano-silicon modified product B are mixed in a solution state, the stirring speed during the mixing process is 100-300 rpm, the stirring time is 20-200 min, and then filtered and dried.

[0030] In a specific implementation process, in S4, the asphalt used is dissolved in a tetrahydrofuran solution to prepare an asphalt solution, and the mass fraction of the asphalt is 5-15wt%.

[0031] The usage ratio of the spherical graphite@silicon composite material to the asphalt solution is 1 g: (0.5-5) mL.

[0032] In the specific implementation process, in the S4, the spherical graphite@silicon composite material is immersed in an asphalt solution at 50~80℃, and then the temperature is increased and stirred at 50~80℃ with a rotation speed of 100~300rpm, and evaporated while stirring until the solvent is completely evaporated to obtain an intermediate product coated with asphalt.

[0033] In a specific implementation process, in S5, the intermediate product is calcined in nitrogen, argon or argon-hydrogen mixed gas, the calcination temperature is 550-800° C., and the calcination time is 30 min-2 h.

[0034] In a specific implementation process, the micron spherical graphite is graphite obtained by granulating natural flake graphite, with a size of about 15 μm, and the size of the nano silicon particles is about 10 to 30 nm.

[0035] Another aspect of the present invention provides a spherical graphite@silicon@carbon composite material prepared by the above-mentioned preparation method of the spherical graphite@silicon@carbon composite material.

[0036] The present invention also provides a use of the spherical graphite@silicon@carbon composite material prepared by the above-mentioned preparation method of the spherical graphite@silicon@carbon composite material as a negative electrode material in a lithium ion battery.

[0037] The specific application process is as follows: Spherical graphite@silicon@carbon composite, conductive carbon black, and polyvinylidene fluoride (PVDF) were uniformly mixed in a mass ratio of 8:1:1. N-methyl-2-pyrrolidone (NMP) was then added dropwise to prepare a slurry, which was then coated onto copper foil. The coated electrode was then placed in a vacuum drying oven and dried at 110°C for 12 hours. After drying, the electrode was sliced into 12 mm diameter circles using a microtome. A Celgard 2500 polypropylene separator was then placed between the positive electrode and the negative lithium metal sheet. 1M LiPF6 in a DEC:EC ratio of 1:1 vol% with 1% FEC electrolyte was then added dropwise. Finally, a lithium-ion battery was assembled to test the electrochemical performance of the composite material.

[0038] In summary, the present invention treats micron-sized spherical graphite with acid to make its surface negatively charged, disperses nano-silicon particles in a cationic surfactant solution to make its surface positively charged, then mixes the negatively charged micron-sized spherical graphite and the positively charged nano-silicon, combines the two together with the help of electrostatic force, and finally disperses the spherical graphite@silicon composite material in an asphalt solution, and obtains a spherical graphite@silicon@carbon composite material after filtering, drying, and calcining.

[0039] like Figure 3 As shown, the present invention also provides a spherical graphite@silicon@carbon composite material prepared by the preparation method of the above-mentioned spherical graphite@silicon@carbon composite material, which uses electrostatic force to ensure the dispersion and adhesion of nano-silicon on the surface of micron-spherical graphite, and at the same time combines the coating effect of asphalt-based carbon material to alleviate the volume expansion of silicon during lithium insertion, thereby improving the cyclic stability of the spherical graphite@silicon@carbon composite material during lithium insertion and deinsertion.

[0040] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0041] The following examples were prepared using conventional instruments and equipment in the art. Experimental methods in the following examples, where specific conditions are not specified, were generally performed under conventional conditions or according to the conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, were conventional commercially available products, with specifications conventional in the art. In the present specification and the following examples, unless otherwise specified, "%" indicates percentage by weight, "part" indicates parts by weight, and "ratio" indicates weight ratio.

[0042] Example 1 100 g of micron-sized spherical graphite was added to 200 mL of 5 wt% sulfuric acid solution and stirred at 100 rpm for 200 min to obtain a negatively charged micron-sized spherical graphite modified product A. 100 g of nano-silicon powder was dispersed in 200 mL of 5 wt% octadecyltrimethylammonium chloride solution and stirred at 300 rpm for 20 min to obtain a positively charged nano-silicon modified product B. The negatively charged micron spherical graphite modified product A was added to the positively charged nano-silicon modified product B, with the mass ratio of spherical graphite to nano-silicon being 100:5. The mixture was stirred at 100 rpm for 200 min, filtered, and dried to obtain a spherical graphite@silicon composite material. 100 g of spherical graphite@silicon composite material was added to a 5 wt% asphalt solution at 50°C. The ratio of spherical graphite@silicon composite material to asphalt was 1 g:0.5 mL. After mixing evenly, the mixture was stirred at 50°C and 100 rpm and evaporated to dryness to obtain an intermediate product. The intermediate product was calcined in nitrogen at a temperature of 550°C for 2 hours. Finally, a spherical graphite@silicon@carbon composite material was obtained. Figure 1 shown.

[0043] Example 2 100 g of micron-sized spherical graphite was added to 1000 mL of 20 wt% hydrochloric acid solution and stirred at 300 rpm for 20 min to obtain a negatively charged micron-sized spherical graphite modified product A; 100 g of nano-silicon powder was dispersed in 1000 mL of 20 wt% 3-aminopropyltriethoxysilane solution and stirred at 300 rpm for 20 min to obtain a positively charged nano-silicon modified product B; The negatively charged micron spherical graphite modified product A was added to the positively charged nano-silicon modified product B, with the mass ratio of spherical graphite to nano-silicon being 100:15. The mixture was stirred at 300 rpm for 20 minutes, filtered, and dried to obtain a spherical graphite@silicon composite material. 100 g of spherical graphite@silicon composite material was added to a 15 wt% asphalt solution at 80°C. The ratio of spherical graphite@silicon composite material to asphalt was 1 g:5 mL. After mixing evenly, the mixture was stirred at 80°C and 300 rpm and evaporated to dryness to obtain an intermediate product. The intermediate product was calcined in an argon-hydrogen mixed gas at a temperature of 800°C for 30 minutes to obtain a spherical graphite@silicon@carbon composite material.

[0044] Example 3 100 g of micron spherical graphite was added to 800 mL of 14 wt% nitric acid solution and stirred at 200 rpm for 100 min to obtain graphite-modified product A; 100 g of nano-silicon powder was dispersed in 600 mL of 15 wt% phenoxyethanol quaternary ammonium salt solution and stirred at 200 rpm for 150 min to obtain a positively charged nano-silicon modified product B; The negatively charged micron spherical graphite modified product A was added to the positively charged nano-silicon modified product B, with the mass ratio of spherical graphite to nano-silicon being 100:10. The mixture was stirred at 150 rpm for 100 minutes, filtered, and dried to obtain a spherical graphite@silicon composite material. 100 g of spherical graphite@silicon composite material was added to a 10 wt% asphalt solution at 60°C. The ratio of spherical graphite@silicon composite material to asphalt was 1 g:4 mL. After mixing evenly, the mixture was stirred at 60°C and 200 rpm and evaporated to dryness to obtain an intermediate product. The intermediate product was calcined in argon at 600°C for 1 hour to obtain a spherical graphite@silicon@carbon composite material.

[0045] Example 4 100 g of micron spherical graphite was added to 300 mL of 10 wt% nitric acid solution and stirred at 200 rpm for 50 min to obtain graphite-modified product A; 100 g of nano-silicon powder was dispersed in 300 mL of 10 wt% hexadecyltrimethylammonium chloride solution and stirred at 200 rpm for 50 min to obtain a positively charged nano-silicon modified product B. The negatively charged micron spherical graphite modified product A was added to the positively charged nano-silicon modified product B, with the mass ratio of spherical graphite to nano-silicon being 100:12. The mixture was stirred at 150 rpm for 200 min, filtered, and dried to obtain a spherical graphite@silicon composite material. 100 g of spherical graphite@silicon composite material was added to a 15 wt% asphalt solution at 80°C. The ratio of spherical graphite@silicon composite material to asphalt was 1 g:2 mL. After mixing evenly, the mixture was stirred at 80°C and 200 rpm and evaporated to dryness to obtain an intermediate product. The intermediate product was calcined in argon at 650°C for 1 hour to obtain a spherical graphite@silicon@carbon composite material.

[0046] Example 5 100 g of micron-sized spherical graphite was added to 500 mL of 14 wt% hydrochloric acid solution and stirred at 200 rpm for 80 min to obtain a negatively charged micron-sized spherical graphite modified product A; 100 g of nano-silicon powder was dispersed in 500 mL of 15 wt% succinic acid monoester quaternary ammonium salt solution and stirred at 200 rpm for 60 min to obtain a positively charged nano-silicon modified product B; The negatively charged micron spherical graphite modified product A was added to the positively charged nano-silicon modified product B, with the mass ratio of spherical graphite to nano-silicon being 100:5. The mixture was stirred at 150 rpm for 200 min, filtered, and dried to obtain a spherical graphite@silicon composite material. 100 g of spherical graphite@silicon composite material was added to a 10 wt% asphalt solution at 60°C. The ratio of spherical graphite@silicon composite material to asphalt was 1 g:5 mL. After mixing evenly, the mixture was stirred at 60°C and 200 rpm and evaporated to dryness to obtain an intermediate product. The intermediate product was calcined in argon at 550°C for 1 hour to obtain a spherical graphite@silicon@carbon composite material.

[0047] Comparative Example 1 100 g of micron-sized spherical graphite was added to 200 mL of 5 wt% sulfuric acid solution and stirred at 100 rpm for 200 min to obtain a negatively charged micron-sized spherical graphite modified product A. 100 g of nano-silicon powder was dispersed in 200 mL of 5 wt% octadecyltrimethylammonium chloride solution and stirred at 300 rpm for 20 min to obtain a positively charged nano-silicon modified product B. The negatively charged micron spherical graphite modified product A was added to the positively charged nano-silicon modified product B, with the mass ratio of spherical graphite to nano-silicon being 100:5. The mixture was stirred at 100 rpm for 200 min, filtered, and dried to obtain a spherical graphite@silicon composite material.

[0048] Comparative Example 2 100 g of spherical graphite was added to 1000 mL of 20 wt% hydrochloric acid solution and stirred at 300 rpm for 20 min to obtain a negatively charged micron spherical graphite modified product A; 100 g of nano-silicon powder was dispersed into the negatively charged micron-spherical graphite modified product A, with the mass ratio of spherical graphite to nano-silicon being 100:15. The mixture was stirred at 300 rpm for 20 min, filtered, and dried to obtain a spherical graphite@silicon composite material.

[0049] Comparative Example 3 100g of micron spherical graphite was directly mixed with nano-silicon at a mass ratio of 100:10, and the mixture was added to a 10wt% asphalt solution at a temperature of 60°C. The ratio of the mixture to the asphalt was 1g:4mL. After mixing evenly, the mixture was stirred at 60°C and 200rpm and evaporated to dryness to obtain an intermediate product. The intermediate product was calcined in argon at 600°C for 1 hour to obtain a spherical graphite@silicon@carbon composite material.

[0050] Figure 1The spherical graphite@silicon@carbon composite material prepared in Example 1 of the present invention and the spherical graphite@silicon composite material prepared in Comparative Example 1 are compared in terms of their cycling performance. As can be seen from the figure, the spherical graphite@silicon@carbon composite material obtained by asphalt coating has a high capacity retention rate during the cycle and has a higher lithium storage specific capacity. The reason is that the nano-silicon in Comparative Example 1 has not been coated with asphalt, and the nano-silicon is very easy to fall off from the spherical graphite during the cycle. Therefore, the comparison result further confirms the necessity of using asphalt-based carbon to anchor nano-silicon.

[0051] Figure 2 The spherical graphite@silicon@carbon composite material prepared in Example 2 of the present invention and the spherical graphite@silicon composite material prepared in Comparative Example 2 are compared in terms of their cycling performance. As can be seen from the figure, the spherical graphite@silicon@carbon composite material obtained by pre-nanosilicon modification and asphalt coating has a high capacity retention rate during the cycle and a higher lithium storage specific capacity. The reason is that the nanosilicon in Comparative Example 2 has not been surface-modified and cannot utilize electrostatic effects to enhance the dispersibility and binding force of the nanomaterial in the spherical graphite. At the same time, due to the lack of the anchoring effect of asphalt-based carbon, the nanosilicon is very easy to fall off from the spherical graphite during the cycle. Therefore, the comparative results further confirm the excellence of the present method.

[0052] Figure 3 The cyclic performance comparison of the spherical graphite@silicon@carbon composite material prepared in Example 3 of the present invention and the spherical graphite@silicon@carbon composite material prepared in Comparative Example 3 shows that the spherical graphite@silicon@carbon composite material obtained by pre-surface modification of spherical graphite and nano-silicon exhibits excellent cyclic stability and high specific capacity, indicating that the spherical graphite and nano-silicon need to be modified before asphalt coating to optimize the dispersion characteristics and adhesion of nano-silicon, thereby improving the cyclic performance of the spherical graphite@silicon@carbon composite material. Therefore, the comparative results further confirm the necessity of surface modification of spherical graphite and nano-silicon.

[0053] The above content is only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a spherical graphite@silicon@carbon composite material, characterized in that: The following steps are involved: The micron spherical graphite and the acid solution are mixed and stirred to perform surface functional modification on the micron spherical graphite to obtain a negatively charged micron spherical graphite modified product A; The nano-silicon particles and the cationic surfactant solution are mixed and stirred to perform surface functional modification on the nano-silicon particles to obtain a nano-silicon modified product B with a positive charge; A negatively charged micron spherical graphite modified product A and a positively charged nano-silicon modified product B are mixed, the positively charged nano-silicon modified product B is dispersed and attached on the surface of the negatively charged micron spherical graphite modified product A, and a spherical graphite@silicon composite material is obtained after filtering and drying; The spherical graphite@silicon composite material is immersed in an asphalt solution, and then the solution is heated to a set temperature while being stirred and evaporated until the solvent is completely evaporated to obtain an intermediate product; The intermediate product is calcined at high temperature to obtain a spherical graphite@silicon@carbon composite material.

2. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, characterized in that: The acid solution is one or more of a sulfuric acid solution, a hydrochloric acid solution, and a nitric acid solution, and the mass fraction of the acid solution is 5-20 wt %.

3. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, wherein: The usage ratio of the micron spherical graphite to the acid solution is 1g: (2-10)mL.

4. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, characterized in that: The cationic surfactant in the cationic surfactant solution is one of octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, phenoxyethanol quaternary ammonium salt, succinic acid monoester quaternary ammonium salt, and 3-aminopropyltriethoxysilane; the solvent in the cationic surfactant solution is water; and the mass fraction of the cationic surfactant solution is 5-20wt%.

5. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, characterized in that: The dosage ratio of the nano-silicon particles to the cationic surfactant solution is 1 g: (2-10) mL.

6. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, characterized in that: The mass ratio of the micron spherical graphite to the nano silicon particles is 100:(5-15).

7. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, characterized in that: The asphalt solution is prepared by compounding asphalt and tetrahydrofuran solution, and the mass fraction of asphalt is 5-15wt%. The usage ratio of the spherical graphite@silicon composite material to the asphalt solution is 1g: (0.5-5)mL.

8. The method for preparing the spherical graphite@silicon@carbon composite material according to claim 1, characterized in that: When the spherical graphite@silicon composite material is immersed in the asphalt solution, the temperature of the asphalt solution is 50~80℃; the set temperature is 50~80℃; The atmosphere for high-temperature calcination is nitrogen, argon or argon-hydrogen mixed gas, the temperature for high-temperature calcination is 550~800℃, and the time for high-temperature calcination is 30min~2h.

9. A spherical graphite@silicon@carbon composite material prepared by the preparation method of the spherical graphite@silicon@carbon composite material according to any one of claims 1 to 8, characterized in that: The structure of the spherical graphite@silicon@carbon composite material is a sandwich structure with spherical graphite as the core, silicon attached to the surface of the spherical graphite, and further coated with pitch-based carbon.

10. Use of the spherical graphite@silicon@carbon composite material prepared by the preparation method of the spherical graphite@silicon@carbon composite material according to any one of claims 1 to 8 as a negative electrode material in a lithium ion battery.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material and preparation method thereof

    CN110931744A